As revistas da SciELO em acesso aberto e as políticas de direitos autorais: o caso das Ciências Agrárias e das Engenharias - Gaban, Nayara de Cassia (Universidade Federal de São Carlos, 2015)
ABSTRACT The aim of this study was to analyze the editorial policies of open access journals indexed in the Scientific Electronic Library Online (SciELO) and in the Directory of Open Access Journals (DOAJ), analyzing which of them require and which do not require the assignment of copyright by the authors, to then find their "levels of openness" as defined in the pamphlet "HowOpenIsIt?" published by SPARC, PLoS and OASPA. To this, data were collected from the policies of Agricultural Sciences and Engineering areas by using the option "Instructions to Authors" contained on the cover page of the titles in the SciELO platform; altogether 155 titles were analyzed, 94 of Agricultural Sciences and 61 of Engineering. Each policy has been examined by the election of keywords relevant according to the aims of the study. The results showed that only ≈4% of the total mentioned clarifies that authors maintain copyright with them, while ≈43% require full transmission of these rights as a prerequisite for publication. The analysis, coupled with bibliographical research, demonstrated that these titles are more “closed", which is not consistent with the definition and essence of Open Access because this focuses on easing scientific diffusion and encourages that research is disseminated as widely as possible, maximizing scientific communication.
SciELO open access journals and copyright policies: the case of Agricultural Sciences and Engineering
Keywords: Copyright; Open access; DOAJ; SciELO; Degrees of openness; Direitos autorais; Acesso aberto; Graus de abertura; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO